FORMULASI DAN KARAKTERISASI GEL KOMBINASI ALOE VERA DAN MENTHOL: FORMULATION AND CHARACTERIZATION OF ALOE VERA AND MENTHOL COMBINATION GEL - Yulyuswarni Yulyuswarni; Ani Hartati; Pudji Rahayu (JFL : Jurnal Farmasi Lampung, 2026)
Abstract Skin inflammation is a common health problem requiring effective management through safe and stable topical formulations. This study aimed to formulate and evaluate the physical characteristics of a topical gel containing a combination of Aloe vera and menthol as a potential anti-inflammatory agent. The gel was prepared using xanthan gum as the base with varying concentrations of Aloe vera powder 200x (0.25%, 0.5%, and 0.75%) and a fixed concentration of menthol (0.5%). The formulations were evaluated for organoleptic properties, homogeneity, pH, spreadability, and stability. The results showed that all formulations exhibited good physical characteristics, were homogeneous, had pH values within the physiological skin range, and demonstrated acceptable spreadability. Statistical analysis indicated that variation in Aloe vera concentration had no significant effect on pH but significantly affected spreadability. Stability testing revealed that the formulations remained relatively stable, although slight color changes occurred at elevated temperatures. These findings suggest that the Aloe vera–menthol gel has potential as a natural-based topical formulation. Keywords: Aloe vera, formulation, gel, menthol, stability